ToxopJasmagondaNia JLLE AND MANCEAUX PADA AYAM BUKAN RAS (Gallus sp.) DAN BURUNG MERPATI (Columba Una Gmelin) DIKOTAMADYA BOGOR - L.E Setyorini; E. Purwaningsih; S. Hartini; J. Aziz (Research Center for Biology-Indonesian Institute of Sciences, 1998)
Using Indirect Hemqiglutination (IHA) test on 26 domesticfowl (Gallus sp.)and domestic pigeon (Columba liviaj were screened